Trainers in continuing VET: emerging competence profile - (:unkn) unknown (Publications Office of the European Union, 2013)
"Cedefop looks at 19 examples of initiatives set up in the Member States on developing competence requirements for trainers in continuing vocational training and adult learning: a brief overview of the practice, its target group(s), main approach and activities, competences required, a link with the validation of non-formal and informal learning, and outcomes, if available. Based on this analysis, an emerging competence profile of a trainer is proposed. The publication builds on Cedefop's work on the changing roles and professional development of VET teachers and trainers and contributes to the work of the thematic working group on the professional development of VET trainers, set up by the European Commission in 2012 and jointly coordinated with Cedefop." (Hrsg., BIBB-Doku)
Keywords: P 3.2.2 Weiterbildner; G 1.2.3.2 Anforderungen & Bedarfe; I 2.2 Europa; Weiterbildner; Anforderungsprofil; Kompetenzprofil; Europa